Wind tunnel and numerical study of a floating offshore wind turbine based on the cyclic pitch control. (July 2021) - Sang, Le Quang; Li, Qing'an; Cai, Chang; Maeda, Takao; Kamada, Yasunari; Wang, Xinbao; Zhou, Shuni; Zhang, Fanghong
Abstract: Offshore wind energy is one of the most important sources of renewable energy to make sure supplying enough electricity for the world in the future. The floating offshore wind turbine (FOWT) operates under many influences such as both the aerodynamic force, the hydrodynamic force and coupled motion between the two. Therefore, in this paper about the effect of collective pitch control and cyclic pitch control on power and loads of FOWT are discussed under the uniform wind velocity of 10 m/s with wind tunnel and numerical investigation. FAST tool (Fatigue, Aerodynamics, Structures, and Turbulence) is used to simulate FOWT under the same wind conditions as wind tunnel experiments. A two-bladed downwind turbine model is used for this experiment to estimate the fluctuations of the power coefficient, thrust coefficient and moments. The pitch moment and the yaw moment are measured at the top of the tower and the fluctuation of loads is compared. The phase angle of the pitch angle is controlled by three actuators through a swash plate equipment. From the simulated results, the effect of the pitch angle change on the power coefficient is higher than the yaw angle change. For the yawed wind condition, the load of the wind turbine at the phase angle of ξ  = 60° was equal to the optimum operating point. Thence, the load of the wind turbine was decreased when the cyclic pitch control method was applied. Highlights: The phase angle of the pitch angle is adjusted by a swash plate. Aerodynamic force is simulated by FAST under the uniform wind condition. Power and thrust coefficients fluctuated when the pitch angle and the yaw angle change. Loads of wind turbine were decreased by the cyclic pitch control method. The simulated results were in good agreement with the experimental data.